Children, health and well-being : policy debates and lived experience - Brady, Geraldine M.; Lowe, Pam; Olin-Lauritzen, Sonja (Sociology of health and illness monograph series., 2015)
This book brings together new and leading scholars, who demonstrate the importance of research with children and from a child perspective, allowing for a fuller understanding of the meaning and impact of health and illness in children's lives.-Demonstrates the importance of research with children and research from a child perspective, in order to fully understand the meaning and impact of health and illness in children's lives -Encourages critical reflection on contemporary health policy and its relationships to culturally specific ways of knowing and understanding children's health -Brings together new and leading scholars in the field of children's health and illness -Moves the highly important issue of children's health into the mainstream sociology of health and illness.